Modern industrial organization theory of media markets and competition policy implications - Oliver Budzinski; Björn Kuchinke (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2018)
This paper outlines the modern industrial organization theory of media markets including competition policy implications. After recapturing fundamentals of industrial organization theory in a non-technical way, the state of the art of (i) modern platform economics, (ii) the economics of the so-called sharing economy, and (iii) the economics of data-based business models and data-driven markets is summarized in a detailed way and illustrated by modern media examples.
Keywords: L0; L82; L10; A2; K21; 330; industrial organization; media economics; industrial economics; platform economics; sharing economy; digital economy; digitization; big data; economics of privacy; competition policy; antitrust economics